O impacto da globalização econômica na efetividade dos direitos humanos: uma análise a partir da teoria do mínimo existencial - Minas, Rodrigo Marchioli Borges (2015)
This study aims to verify the effectiveness of human rights, here understood in its varied and interconnected dimensions, before one of the phenomena that most affected them: economic globalization. To understand the way this impact occurs, it is necessary to comprehend human rights from their historical foundations and, subsequently, in its scope and breadth. Therefore, it is made a chronological analysis of historical developments of human rights and, hence, philosophical and normative, from the bourgeois revolutions of 1787 and 1789, to the current period. Delimited its scope and breadth, takes place a foray into economic globalization to, at first, define the range of the phenomenon; and then, to see against what economic globalization is putting itself and how it affected the effectiveness of human rights, from three main effects: benefits from comparative advantages, substitution of traditional centres of power and markets financialization. From this perspective, markedly, above all, of ineffectiveness of human rights, it seeks to establish certain ethical and politically fair boundaries for human rights on which economic globalization cannot overcome, from the perspective of the theory of existential minimum